A survey of VASNET framework to provide infrastructure-less green iots communications for data dissemination in search and rescue operations - Jambli, Mohamad Nazim; Khan, Adnanshahid; Shoon, Sia Chiu (University of Electronic Science and Technology of China, 2016)
The implementation of wireless technologies based on the vehicular ad hoc sensor network (VASNET) may provide support for the search and rescue (SAR) team to operate effectively in natural disaster events, such as landslide, earthquake, flooding, and tsunami. The operations of SAR team are very challenging in such events due to the possible damages of the existing telecommunication infrastructures. The existing deployment of the cellular communications infrastructure may be partially or completely destroyed after the occurrence of these natural disasters. Thus, the current VASNET infrastructure must be able to support the infrastructure-less network by integrating other green wireless technologies that can benefit the SAR team, which can indirectly save more human lives and reduce the number of casualties. Therefore, the integration of green Internet of things (IoT) and VASNET is proposed to form a heterogeneous framework for data dissemination in SAR operations. In addition, this paper also discusses the existing IoT framework in disaster scenarios with future research direction for IoT using on any aspect, especially related to the natural disaster scenarios